1995
DOI: 10.1117/12.212026
|View full text |Cite
|
Sign up to set email alerts
|

Coherent laser radar for vibrometry: robust design and adaptive signal processing

Abstract: A coherent laser radar system based on semiconductor laser technology has been designed and built. The compact design and the absence of adjustments makes the system mechanically robust and easy to use. The present system has an output power of 50 mW and a line width of 280 kHz (HWHM). The laser radar system has been used in vibrometry measurements. For vibrometry of moving objects, adaptive signal processing is required in order to obtain the vibration signature. Especially for unresolved objects, interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Finally, we should emphasize that the analysis reported here is based on well-established models for speckle and additive noise although with a somewhat idealized model for the demodulator. This is in line with the approach which has been adopted by previous authors and which has been shown to be consistent with experimental data [6][7][8]. We are currently undertaking experiments to test the validity of our results in the low carrier-to-noise ratio regimes which have not been analysed thoroughly before.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, we should emphasize that the analysis reported here is based on well-established models for speckle and additive noise although with a somewhat idealized model for the demodulator. This is in line with the approach which has been adopted by previous authors and which has been shown to be consistent with experimental data [6][7][8]. We are currently undertaking experiments to test the validity of our results in the low carrier-to-noise ratio regimes which have not been analysed thoroughly before.…”
Section: Discussionsupporting
confidence: 90%
“…The principles of laser vibration sensing have been described in detail elsewhere [6][7][8]. The optical set-up is illustrated schematically in figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…We aim to compare the performance of our algorithm with that of the microdoppler developed in Renhorn et al (1995) and classically used in laser vibrometry to analyse the vibrations of an object with a translation motion. Further details concerning its implementation can be found in Le´vy-Leduc (2004).…”
Section: Comparison With the Microdoppler On Laser Vibrometry Signalsmentioning
confidence: 99%
“…We will see in this section that the penalized cumulated periodogram provides an accurate estimation of at SNR much smaller than those required by the microdoppler approach, which is a classical method used in laser vibrometry for specific signals like (12) (more details on the microdoppler method can be found in [12] and [18]). This is an important point in practice, because it means that the vibration analysis can be achieved even if the vibrating object is far from the laser.…”
Section: Some Monte Carlo Experiments On Different Synthetic Vibrmentioning
confidence: 99%